Design and optimization of a high power density machine for flooded industrial pump - Al-Timimy, A.; Degano, Michele; Giangrande, Paolo; Lo Calzo, Giovanni; Xu, Zeyun; Galea, Michael; Gerada, C.; Zhang, He; Xia, Liqm (2016)
This paper presents the design optimization procedure of a high power-density, permanent magnet synchronous machine for industrial pump applications. The designed machine drives an electric, oil flooded pump. In order to achieve higher torque-density, a fractional slot machine (8 poles, 9 slots) with double layer (concentrated) winding has been selected after a preliminary trade-off study, which considered several slot/pole combinations and winding configurations. The developed machine provides low torque ripple and short end windings, which contribute to lower axial length and higher efficiency. The electromagnetic performances have been evaluated by using finite element method and the lamination geometry has been optimized through a genetic. The final results are presented highlighting the achieved design targets.